Existence of positive solutions for singular impulsive differential equations with integral boundary conditions on an infinite interval in Banach spaces - Xu Chen; Xingqiu Zhang (Electronic Journal of Qualitative Theory of Differential Equations, 2011)
In this paper, the Mönch fixed point theorem is used to investigate the existence of positive solutions for the second-order boundary value problem with integral boundary conditions of nonlinear impulsive differential equations on an infinite interval in a Banach space.